Mezi skrytým a konvenčním. Kenneth Burke a teorie symbolu - Martin Švantner; Marianna Abrahamyan (Slovo a Smysl, 2022)
This article discusses Kenneth Burke’s theory of the symbol, which considers the use of the sign as a specifically human activity associated with the formation of meaning. In Burke’s view, the symbol is a meaning-making device that can influence human action and thoughts, and therefore represents the key to understanding the nature of human communication. In this article, Burke’s ideas are compared to other sign-symbol theories — namely, the semiotics of Umberto Eco and Juri Lotman, Charles Sanders Peirce’s semeiotics, as well as Ernst Cassirer’s philosophy of symbolic forms —, with analysis on the way each of these theorists defines the nature of the symbol and its conventional acceptation, principle of identification, and the characteristics of the symbolisation process itself.